Surgical Treatment of Posttraumatic Radioulnar Synostosis. (8th February 2016) - Pfanner, S.; Bigazzi, P.; Casini, C.; De Angelis, C.; Ceruso, M.
Abstract : Radioulnar synostosis is a rare complication of forearm fractures. The formation of a bony bridge induces functional disability due to limitation of the pronosupination. Although the etiology of posttraumatic synostosis is unknown, it seems that the incidence is higher in patients who have suffered a concomitant neurological or burn trauma, and extensive soft tissue injury, mainly due to high-energy impact. Surgical treatment, such as reinsertion of distal biceps tendon into the radius, seems to be another possible factor. The aim of the surgical treatment is to remove the bony bridge and restore complete range of movement (ROM), thus preventing recurrence. Literature does not indicate a preferred type of surgical procedure for the aforementioned complication; however, it has been shown that surgical interposition of inert material reduces the formation rate of recurrent bony bridge. We describe a surgical technique in two cases in which the radius and ulna were wrapped with allogenic, cadaver fascia lata graft to prevent bony bridge formation. The data from 2 years of follow-up are reported, indicating full restoration of ROM and no recurrence of synostosis.